MODEL FRAMING SEBAGAI KOMUNIKASI STATEGIS UNTUK MENDUKUNG IMPLEMENTASI TEKNOLOGI PADA PEMBELAJARAN MENDALAM DI SEKOLAH - Thalib, Darmawan (STKIP Pesisir Selatan, 2025)
Framing is a strategic approach in education that shapes stakeholders’ perspectives and interpretations of educational issues, policies, and practices. In the context of digital transformation in Indonesian education, framing serves as a critical instrument to support the implementation of technology that facilitates deep learning. This study aims to develop a framing model that enhances the adoption of educational technology in schools, focusing on improving teachers’ technological competencies and the effectiveness of strategic communication within educational environments. The research employs a conceptual literature review using content analysis of recent studies and scholarly literature. The findings reveal that an effective framing model consists of three key stages: diagnostic framing, which identifies challenges in technology integration; prognostic framing, which formulates pedagogical solutions based on technology; and motivational framing, which builds collective commitment towards digital transformation in schools. These findings emphasize that framing strategies can enhance collective awareness, strengthen collaboration, and promote the sustainable implementation of innovative deep learning practices. This model is expected to serve as a practical reference for school leaders, teachers, and policymakers in advancing the digital transformation of education in Indonesia.